2021
DOI: 10.1038/s41401-021-00657-w
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide suppresses the growth and metastasis of non-small cell lung cancer by inhibiting β-catenin-mediated epithelial–mesenchymal transition

Abstract: Non-small cell lung cancer (NSCLC) is characterized by a high incidence of metastasis and poor survival. As epithelial–mesenchymal transition (EMT) is well recognized as a major factor initiating tumor metastasis, developing EMT inhibitor could be a feasible treatment for metastatic NSCLC. Recent studies show that triptolide isolated from Tripterygium wilfordii Hook F attenuated the migration and invasion of breast cancer, colon carcinoma, and ovarian cancer cells, and EMT played important roles in this proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In a step-wise strategy, we first assessed the effects of triptolide and gemcitabine combined with paclitaxel in PDAC cell monocultures grown in different hydrogels and found that triptolide was effective against MIA PaCa-2 cells but not PANC-1 cells. These differential responses may be explained by the anti-proliferative effects of triptolide on mesenchymal-like cells and an epithelial-mesenchymal transition ( 58 ). In contrast, gemcitabine and paclitaxel treatment exhibited lower efficacy in the PDAC cell monocultures, in particular MIA PaCa-2 cells, in the stiffer collagen-nanocellulose matrices compared to the soft collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In a step-wise strategy, we first assessed the effects of triptolide and gemcitabine combined with paclitaxel in PDAC cell monocultures grown in different hydrogels and found that triptolide was effective against MIA PaCa-2 cells but not PANC-1 cells. These differential responses may be explained by the anti-proliferative effects of triptolide on mesenchymal-like cells and an epithelial-mesenchymal transition ( 58 ). In contrast, gemcitabine and paclitaxel treatment exhibited lower efficacy in the PDAC cell monocultures, in particular MIA PaCa-2 cells, in the stiffer collagen-nanocellulose matrices compared to the soft collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that triptolide can regulate EMT in cancer progression by inhibiting the Wnt/β-catenin pathway, thus inhibiting the migration and invasion of tumor tissues ( Liu et al, 2015 ; Basu et al, 2018 ). Deng et al (2021) found that after triptolide treatment, the expression of the epithelial marker E-cadherin in NCI-H1299 cells was significantly increased, while the expressions of mesenchymal markers ZEB1, vimentin, and slug were decreased, and the expression of β-catenin was also inhibited. The researchers overexpressed and knocked out genes in NCI-H1299 and NCI-H460 cells, respectively, and β-catenin confirmed that inhibition of EMT is mediated by β-catenin.…”
Section: Mechanism Of Triptolide On Non–small Cell Lung Cancermentioning
confidence: 94%
“…Diverse cellular events, including apoptosis, cellular senescence, and EMT, are influenced by triptolide [ 207 , 208 , 209 ], connoting its therapeutic benefit against cancer. Further, triptolide can attain its anti-pancreatic cancer activity via imposing limits on HIF-1α expression in vitro and in vivo [ 184 ].…”
Section: Terpene Phytochemicalsmentioning
confidence: 99%